DEVELOPMENT OF THE VIRTUE OF ENLIGHTENMENT IN STUDENTS THROUGH THE JOURNALISTIC WORKS OF A.AVLONI (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The journalistic works of Abdulla Avloni play a vital role in fostering enlightenment in students by emphasizing education, moral integrity, and social responsibility. His writings advocate for modern pedagogy, ethical leadership, and critical thinking. Avloni’s principles remain relevant in contemporary education, encouraging civic engagement and intellectual growth. By integrating his ideas into curricula, educators can inspire students to pursue lifelong learning and contribute to national progress through knowledge and ethical leadership, ensuring the development of a socially responsible generation.